The flottweg drupalm process - commercially realized installations and options for producing a mixed drupalm oil or separate oils - Paterson, S.L. (Malaysian Palm Oil Board (MPOB), 2015)
Flottweg, together with her collaborators in France, Malaysia and other countries, has developed a process of continuous palm oil extraction whereby whole palm fruits are disintegrated and a mixed oil is extracted using three phase tricanter technology. This paper will provide details on the process, the technical and commercial developments that have occurred over the last few years, and also introduce a modified Druplam process where palm kernels are separated prior to entering the Drupalm process, thereby yielding separate oils.